Application of headless cannulated compression screws for treatment of Delbet-Colonna II and III femoral neck fractures in children - Jiang, Yikun; Wang, Yanbing; Peng, Chuangang; Yuan, Baoming; Wu, Dankai (Frontiers in Pediatrics, 2025)
PurposeFemoral neck fractures are clinically rare and are associated with a high risk of complications in children. Traditional internal fixation implants such as Kirschner wires and partial-thread cannulated screws (PTCS) have complications such as screw withdrawal and internal fixation failure. To address this problem, in this study we investigated the effectiveness of headless cannulated compression screws (HCCS) in the treatment of femoral neck fractures in children patients.MethodsChildren diagnosed with Delbet-Colonna II or III femoral neck fracture treated by closed reduction and percutaneous fixation with HCCS were retrospectively reviewed. The extent of fracture reduction and postoperative hip function were assessed according to the Haidukewych standard and with the Harris score, respectively. Postoperative complications were recorded.ResultsAccording to the inclusion criteria and exclusion criteria in this retrospective study, A total of 12 patients (8 males and 4 females) aged 3–14 years (average age: 8.3 years) were reviewed. The mean blood loss from surgery was 34.58 ± 9.40 ml and mean operation time was 102.50 ± 32.72 min. Overall, fracture reduction was achieved in most cases, with 7 that were excellent (58.33%) and 5 that were good (41.67%) according to the Haidukewych standard. The average follow-up period was 24.67 months. Radiographic analysis revealed an average time for fracture healing of 8.58 ± 3.87 weeks. Harris score was 88.67 ± 2.61 at 3 months after surgery, and increased to 92.25 ± 1.91 at the 6-month follow-up; excellent outcomes were achieved at the last follow-up evaluation (95.17 ± 1.95). No surgery-related complications were reported during the follow-up period.ConclusionsWe recommend closed reduction and internal fixation with HCCS as a feasible alternative for the treatment of Delbet-Colonna II and III femoral neck fractures in children.